Pictorial health warnings on cigarette packs and the impact on women - Lorna Bittencourt; Sharina D Person; Regina Celina Cruz; Isabel C Scarinci (Universidade de São Paulo, 2013)
OBJECTIVE : To analyze the association between the pictorial graphic health warnings on cigarette packs and their impact on intention to quit smoking among women. METHODS : Population-based cross-sectional study among 265 women daily smokers in the State of Paraná in 2010. The sample size was calculated using cluster sampling. Participants were asked whether they had seen any pictorial graphic health warnings in the past 30 days, whether these warnings made them think about quitting, and intensity of these thoughts. The data was analyzed using logistic regression and the independent variables included age, educational attainment, whether they had children, whether they had attempted to quit smoking in the past 12 months, age of smoking initiation, number of cigarettes smoked per day, their town of residence, and how soon after waking do they smoke their first cigarette. RESULTS : Participants (91.7%) reported seeing the pictorial graphic health warnings in the past 30 days. Women with elementary education or below and women with some/complete high school education were more likely to think about quitting smoking after seeing the pictorial graphic health warningsthan women with higher education (OR = 4.85; p = 0.0028 and OR = 2.91; p = 0.05), respectively). Women who attempted to quit smoking in the past 12 months were more likely to think about quitting than women who had not (OR = 2.49; p = 0.001). Quit attempts within the last 12 months were associated with intensity of these thoughts (OR = 2.2; p = 0.03). CONCLUSIONS : Results show an association between pictorial graphic health warnings and intent to quit smoking among women with warnings having a greater impact among women with less education and who had attempted to quit smoking within the past year. Tobacco control strategies should be implemented across all groups of women regardless of their educational attainment.